Effect of pharmaceutical promotion and incentives offered by pharmaceutical companies on the prescribing pattern of medical students: a cross-sectional study from a developing nation Pakistan - Gillani, Ali Hassan; Arshad, Hafsa; Umer, Muhammad Farooq; Arshed, Muhammad; Khan, Farman Ullah; Bashir, Kamran; Xu, Sen; Mujtaba, Hasan; Mohamed Ibrahim, Mohamed Izham; Fang, Yu (Frontiers in Medicine, 2024)
Pharmaceutical companies continuously pursue health-care professionals, starting from the medical college level, which can ultimately lead to irrational prescribing of drugs and antibiotics. Therefore, our main aim was to evaluate the opinions and attitudes of medical students toward pharmaceutical promotion.This study utilized a cross-sectional online survey that applied the snowball sampling technique. Data were collected from three public and three private sector medical colleges in Punjab Pakistan using snowball sampling. A modified version of a pre-structured questionnaire was used to collect data between October 2020 and January 2021. Medical students from the 3 rd year onward were captivated. The tool was made available on google forms and students could access it by clicking the link shared. The effect of promotion on prescribing pattern and future prescribing of antibiotics.Descriptive statistics, chi square, t-test were used to analyze the data.The study reveals that only small students are willing to engage in promotional activities, accepting rewards, which influences their choice towards selection of drugs and antibiotics. This study also underscored the necessity of giving proper educational instructions regarding promotion to medical students. This study focused on the educational prerequisites of the students.